Project management of multiple projects and contracts - Loftus, Jack (Thomas Telford, 1999)
This work provides detailed guidance on how to project manage multiple projects, and advises on the standard contracts which should be used. It aims to assist engineers and managers, offering guidance and step-by-step accounts.